Hi tech support end to end drought monitoring and management system for South Asia - International Water Management Institute (International Water Management Institute, 2022)
Every year, drought impacts millions of people worldwide, including in South Asia. Since 1990, affecting over 750 million people, with economic damages estimated at 7 billion USD. Mitigating drought risks helps support vulnerable communities to face the effects and impacts of drought conditions, through enhancing coping capacities such as preventive measures at the sub-national or local levels.